The Quality of Illuvè Fashion as a Transformative Design in the Context of Contemporary Aesthetics - Sofia Widhayanti; Sri Endah Wahyuningsih (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
Systematic studies that comprehensively assess the quality of a single transformable fashion design remain limited, particularly within the context of student experimental projects, while contemporary fashion demands designs that are adaptive, aesthetic, and sustainable. This research aims to describe the quality of Illuvè as a transformable fashion design within the framework of contemporary aesthetics. The study employed a quantitative descriptive approach, with Illuvè serving as the research object and expert panelists, as well as trained panelists, as subjects. The quality of the fashion design was evaluated based on five indicators: design, aesthetics, sewing technique, performance, and uniqueness. The results show that Illuvè’s quality falls into the highly feasible category, with an overall average score of 96% from both expert and trained panelists. The highest score was achieved in the uniqueness indicator at 98%, while the lowest was in the sewing technique indicator at 95%. The evaluation further indicates that both Look 1 and Look 2 are equally categorized as highly feasible, with the transformation system successfully maintaining structural stability, aesthetics, and functionality. The novelty of this research lies in its evaluation of the quality of a single transformable fashion design as an individual object through structured product quality indicators. The findings provide academic implications by strengthening studies on the evaluation of transformable fashion design quality, as well as practical implications for fashion designers in developing adaptive transformable designs without compromising visual and construction quality.